Volatiles Mediated Interactions Between Aspergillus oryzae Strains Modulate Morphological Transition and Exometabolomes - Singh, Digar; Lee, Choong H. (Frontiers in Microbiology, 2018)
Notwithstanding its mitosporic nature, an improbable morpho-transformation state i.e., sclerotial development (SD), is vaguely known in Aspergillus oryzae. Nevertheless an intriguing phenomenon governing mold's development and stress response, the effects of exogenous factors engendering SD, especially the volatile organic compounds (VOCs) mediated interactions (VMI) pervasive in microbial niches have largely remained unexplored. Herein, we examined the effects of intra-species VMI on SD in A. oryzae RIB 40, followed by comprehensive analyses of associated growth rates, pH alterations, biochemical phenotypes, and exometabolomes. We cultivated A. oryzae RIB 40 (S1VMI: KACC 44967) opposite a non-SD partner strain, A. oryzae (S2: KCCM 60345), conditioning VMI in a specially designed 'twin plate assembly'. Notably, SD in S1VMI was delayed relative to its non-conditioned control (S1) cultivated without partner strain (S2) in twin plate. Selectively evaluating A. oryzae RIB 40 (S1VMI vs. S1) for altered phenotypes concomitant to SD, we observed a marked disparity for corresponding growth rates (S1VMI<S1)7 days, media pH (S1VMI>S1)7 days, and biochemical characteristics viz., protease (S1VMI>S1)7 days, amylase (S1VMI>S1)3-7 days, and antioxidants (S1VMI>S1)7 days levels. The partial least squares - discriminant analysis (PLS-DA) of gas chromatography - time of flight - mass spectrometry (GC-TOF-MS) datasets for primary metabolites exhibited a clustered pattern (PLS1, 22.04%; PLS2, 11.36%), with 7 days incubated S1VMI extracts showed higher abundance of amino acids, sugars, and sugar alcohols with lower organic acids and fatty acids levels, relative to S1. Intriguingly, the higher amino acid and sugar alcohol levels were positively correlated with antioxidant activity, likely impeding SD in S1VMI. Further, the PLS-DA (PLS1, 18.11%; PLS2, 15.02%) based on liquid chromatography - mass spectrometry (LC-MS) datasets exhibited a notable disparity for post-SD (9-11 days) sample extracts with higher oxylipins and 13-desoxypaxilline levels in S1VMI relative to S1, intertwining Aspergillus morphogenesis and secondary metabolism. The analysis of VOCs for the 7 days incubated samples displayed considerably higher accumulation of C-8 compounds in the headspace of twin-plate experimental sets (S1VMI:S2) compared to those in non-conditioned controls (S1 and S2 - without respective partner strains), potentially triggering altered morpho-transformation and concurring biochemical as well as metabolic states in molds.